3-Deazaadenosine-induced disorganization of macrophage microfilaments. - Stopford, C R (1985)
3-Deazaadenosine (c3Ado) has been reported to inhibit a number of cellular functions. These biological effects of c3Ado have generally been attributed to its ability to act as inhibitor and substrate of S-adenosylhomocysteine hydrolase. In this report, it is revealed by fluorescence microscopy that c3Ado caused disorganization of the microfilament system of mouse macrophages at concentrations (greater than or equal to 5 microM) similar to those that inhibited antibody-dependent phagocytosis and zymosan-stimulated H2O2 production by these cells. Inhibition of phagocytosis and perturbation of microfilaments by c3Ado were completely abrogated by washing the macrophages free of this agent and allowing the cells a 30-min recovery period. Furthermore, these effects of c3Ado on phagocytosis and microfilaments appeared to be independent of the increase in S-adenosylhomocysteine and S-3-deazaadenosylhomocysteine that occurred in these macrophages. First, periodate-oxidized adenosine and 3-deaza(+/-)aristeromycin, two other inhibitors of S-adenosylhomocysteine hydrolase that caused greater increases in macrophage S-adenosylhomocysteine than did c3Ado, had no effect on either phagocytosis or microfilaments. Second, pretreatment of macrophages with periodate-oxidized adenosine (to inhibit S-adenosylhomocysteine hydrolase) prevented the subsequent metabolism of c3Ado to S-3-deazaadenosylhomocysteine but did not diminish the effects of c3Ado on phagocytosis or microfilaments. These results demonstrate that c3Ado can perturb the microfilament system of cells and provide an alternative mechanism for the biological effects of c3Ado.